The Effect of Inflation and Exchange Rate on the Indonesian Sharia Stock Index (ISSI) Period 2013-2022 - Nufzatutsaniah; Siti shalma (Al-Maqrizi: Jurnal Ekonomi Syariah dan Studi Islam, 2024)
This study aims to determine and examine the effect of inflation and exchange rates on the Indonesian Sharia Stock Index (ISSI) for 2013-2022. The method used in this research is the Quantitative method with the causal associative approach. The data source used in this study uses secondary data. The selected population is the entire movement of the Indonesian Sharia Stock Index (ISSI), Inflation and Exchange Rate data, with the sample used being Inflation, Exchange Rate and Indonesian Sharia Stock Index (ISSI) data for 2013-2022. The analysis methods used are descriptive tests, classical assumption tests, simple and multiple linear regression analyses, hypothesis testing, coefficient of determination, and correlation. The results showed that partial inflation had no effect and was insignificant to the Indonesian Sharia Stock Index (ISSI) for the period 2013-2022; the Exchange Rate partially had an impact and was significant to the Indonesian Sharia Stock Index (ISSI) for the period 2013-2022. Simultaneous test results show that Inflation and Exchange Rates together (simultaneously) significantly affect the Indonesian Sharia Stock Index (ISSI) for the 2013-2022 Period.